Gambaran Tingkat Kecemasan pada Korban Banjir Bandang di Kabupaten Magelang - Dewa Ayu Made Dewi Widhayanti; Sri Warsini; Sutono Sutono (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2018)
Background: Indonesia is one of the countries that is prone to flood disaster. The flash flood that occurred in Magelang on April 29th 2017 had caused a major physical loss, such as houses damage, dead casualties, injured victims, and displacement. In addition to the physical loss, flood disaster may impact mental health of the victims e.g. stress, anxiety, depression and post-trauma stress disorder.Objective: This research was aimed to identify the anxiety level of the victim of flood at Sambungrejo and Citrosono villages and the difference of anxiety level of flood victim based on the characteristics of the respondents.Methods: This research was a descriptive research with a cross sectional design. A cluster sampling was performed to get 100 respondents who were victim of flood in Sambungrejo and Citrosono villages, which met the inclusion and exclusion criteria of this study. The instruments used in this study were Zung Self Anxiety Scale (ZSAS) and socio-demographic questionnaire. The data were analyzed using Fisher test.Results: The research found that 91% of respondents did not suffer anxiety, while the rest of the respondents (9%) suffered mild - moderate anxiety, thus no respondents suffered severe anxiety. The variation of respondent anxiety level occured based on evacuation record at p value = 0,026.Conclusion: Overall, the flood victims in Sambungrejo and Citrosono villages did not suffer anxiety. Among all factors, evacuation record correlated with the anxiety level of respondents. ABSTRAKLatar Belakang: Indonesia merupakan salah satu negara yang rawan terhadap bencana banjir. Banjir bandang yang terjadi di Magelang pada 29 April 2017 menimbulkan kerugian berupa kerusakan rumah, korban meninggal, korban luka–luka dan mengungsi. Selain dampak secara fisik, banjir dapat memberikan dampak bagi kesehatan mental berupa stres, kecemasan, depresi, dan gangguan stres pascatrauma.Tujuan: Penelitian ini bertujuan untuk mengetahui tingkat kecemasan korban di Desa Sambungrejo dan Citrosono setelah banjir bandang dan mengetahui perbedaan tingkat kecemasan berdasarkan karakteristik responden.Metode: Penelitian ini merupakan penelitian deskriptif dengan rancangan cross sectional. Sampel pada penelitian ini adalah korban banjir bandang di Desa Sambungrejo dan Citrosono yang memenuhi kriteria inklusi dan eksklusi sejumlah 100 orang. Teknik sampling yang digunakan adalah cluster sampling. Instrumen yang digunakan adalah Zung Self-Rating Anxiety Scale (ZSAS) dan kuesioner karakteristik responden. Analisis data menggunakan uji Fisher.Hasil: Hasil penelitian menunjukkan 91% responden tidak mengalami kecemasan, sisanya sebanyak 9% responden mengalami kecemasan ringan hingga sedang, dan tidak ada responden yang mengalami kecemasan parah. Tingkat kecemasan responden hanya berbeda berdasarkan riwayat mengungsi dengan nilai p = 0,026.Kesimpulan: Secara keseluruhan korban banjir bandang di Desa Sambungrejo dan Citrosono tidak mengalami kecemasan. Dari semua faktor yang ada, hanya riwayat mengungsi yang berhubungan dengan tingkat kecemasan responden.